MODEL INTERNALISASI NILAI-NILAI AGAMA ISLAM PADA KEGIATAN PRAMUKA DI MADRASAH TSANAWIYAH - Oktio Frenki Biantoro (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2021)
The internalization of Islamic religious values so far has only been carried out in classroom learning activities so that there is no synergy between Islamic religious values and scouting activities. This study aims to determine Islamic religious values in Madrasah Tsanawiyah (MTs), how to internalize Islamic religious values in scouting activities at Madrasah Tsanawiyah, and the impact of internalizing Islamic religious values on scouting activities at Madrasah Tsanawiyah. To carry out the research, the researchers used a qualitative approach. This research was carried out at MTs Ma'arif Balong Ponorogo by taking the object of Teacher Scouts in the internalization of Islamic religious values. In conducting this research, the type of research chosen is qualitative. To collect data from the various sources mentioned above, several methods were used, namely in-depth interviews, observation, and documentation. Then for the data analysis technique, the Miles and Huberman Interactive Data Analysis Model. The results of this study are (1) Islamic religious values at MTs Ma'arif Balong Ponorogo, namely the value of worship, moral values, and social values, (2) how to internalize Islamic religious values in scouting activities at MTs Ma'arif Balong Ponorogo namely by using the method of religious habituation and memorization, and (3) the impact of internalizing Islamic religious values on scout activities at MTs Ma'arif Balong Ponorogo, namely increasing faith, piety, worship, exemplary, and improving student morals.